1996
DOI: 10.1210/endo.137.5.8612522
|View full text |Cite
|
Sign up to set email alerts
|

Molecular cloning and functional characterization of a rat pituitary G protein-coupled adenosine triphosphate (ATP) receptor.

Abstract: There is increasing evidence that pituitary ATP receptors may play a novel role in modulating pituitary function. This work reports the isolation and expression of a pituitary ATP receptor gene clone from a rat pituitary complementary DNA library. The isolated clone (rpP2U) has a 1125-bp coding sequence flanked by 483 bp of 5' - and 422 bp of 3'-untranslated sequences. The deduced 374-amino acid product shows structural features common to other G protein-coupled receptors, and when stably transfected into a gl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
47
1

Year Published

1996
1996
2011
2011

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 74 publications
(50 citation statements)
references
References 1 publication
2
47
1
Order By: Relevance
“…UTP-sensitive receptors have been suggested to be present in gonadotrophs [16,26] and lactotrophs [17], but these results were not confirmed by other reports [2,14]. The present results showed that gonadotrophs and lactotrophs express P2Y 4 and P2Y 2 receptors, respectively, the ligand for which is UTP, confirming that gonadotrophs and lactotrophs express UTP-sensitive receptors.…”
Section: Discussioncontrasting
confidence: 95%
See 1 more Smart Citation
“…UTP-sensitive receptors have been suggested to be present in gonadotrophs [16,26] and lactotrophs [17], but these results were not confirmed by other reports [2,14]. The present results showed that gonadotrophs and lactotrophs express P2Y 4 and P2Y 2 receptors, respectively, the ligand for which is UTP, confirming that gonadotrophs and lactotrophs express UTP-sensitive receptors.…”
Section: Discussioncontrasting
confidence: 95%
“…Following RT-PCR analysis, P2Y 1 , P2Y 2 , P2Y 4 , P2Y 6 , and P2Y 12 receptor transcripts were detected in mixed anterior pituitary cells [13,14]. The identified cells in the anterior pituitary with P2Y receptors were also found in rat pituitary folliculo-stellate cells in primary culture [15], gonadotrophs [16] and lactotrophs [17]. No detailed immunofluorescence, Western blot or in situ hybridization studies about P2Y receptor subtype expression on the individual cell types in the anterior pituitary are currently available.…”
Section: Introductionmentioning
confidence: 93%
“…The sequencing analysis revealed that the PCR product of this major band was an alternative splice variant lacking 72 bp (nt 339-410 in GenBank accession number X97328). In metabotropic P2Y receptor subtypes, amplification of P2Y 1 , P2Y 2 , P2Y 4 and P2Y 6 receptor subtypes genes resulted in single bands around the predicted sizes of 415, 359, 352 and 313 bp, respectively, and PCR products were found to show 100 % homology for the sequences reported previously (Chang et al 1995;Tokuyama et al 1995;Chen et al 1996;Bogdanov et al 1998). The expression of P2Y 11 receptor subtype gene was not detected by using human P2Y 11 primers in these rat brown adipocytes.…”
Section: Expression Of P2x and P2y Receptor Subtypes Genes In Culturementioning
confidence: 61%
“…Single strand cDNA was synthesized from 5 mg of total RNA with 20 units of RAV-2 reverse transcriptase (Takara Biochemicals, Kyoto, Japan) using random primers. A portion of cDNA was amplified by the polymerase chain reaction (PCR) method using rat P2X 1 -, P2X 2 , P2X 3 -, P2X 4 -, P2X 5 -, P2X 6 -, P2X 7 -, P2Y 1 -, P2Y 2 -, P2Y 4 -, P2Y 6 -and human P2Y 11 -specific primers synthesized according to the nucleotide sequences of rat receptor genes P2X 1 (GenBank accession number X80477) (Valera et al 1994), P2X 2 (GenBank accession number U14414) (Brake et al 1994), P2X 3 (GenBank accession number X90651) (Chen et al 1995), P2X 4 (GenBank accession number U47031) (Wang et al 1996), P2X 5 (GenBank accession number X97328) (Garcia-Guzman et al 1996), P2X 6 (GenBank accession number X92070) (Collo et al 1995), P2X 7 (GenBank accession number X95882) (Surprenant et al 1996), P2Y 1 (GenBank accession number U22830) (Tokuyama et al 1995), P2Y 2 (GenBank accession number L46865) (Chen et al 1996), P2Y 4 (GenBank accession number Y14705) (Bogdanov et al 1998), P2Y 6 (GenBank accession number D63665) (Chang et al 1995) and P2Y 11 (GenBank accession number AF030335) (Communi et al 1997), respectively: P2X 1 sense, 5‚-CCC-AGAAGGTGGCATATGCCAG-3‚ (nt 569-590); P2X 1 antisense, 5‚-CAGTCCAGATCACACTTCCAGTC-3‚ (nt 1003-981); P2X 2 sense, 5‚-ATCCTCATCAAGAACAGCATCCAC-3‚ (nt 589-612); P2X 2 antisense, 5‚-TTGGCAAACCTGAAGTTGTAGCCT-3‚ (nt 914-891); P2X 3 sense, 5‚-CTGTGAGATCCAGGGCTGGTG-3‚ (nt 619-639); P2X 3 antisense, 5‚-GGATGCCAAAAGCCT-TCAGGAG-3‚ (nt 1091-1070); P2X 4 sense, 5‚-AACATGATT-GTCACCGTGAACCAG-3‚ (nt 340-363); P2X 4 antisense, 5‚-TGCCATCACCTGGAAGCTATGTC-3‚ (nt 771-749); P2X 5 sense, 5‚-GACACTTCCCTGCAGAGTGCTG-3‚ (nt 225-246); P2X 5 antisense, 5‚-AAGGGGATCCGTTGGCATGGAC-3‚ (nt 593-572); P2X 6 sense, 5‚-GTAACCCAGGTTAAGGAACTG-GAG-3‚ (nt 239-262); P2X 6 antisense, 5‚-GTATCTAAG-GCATTGGTTCTGGAG-3‚ (nt 622-645); P2X 7 sense, 5‚-TCT-TCGACACGGCCGACTACAC-3‚ (nt 381-402); P2X 7 antisense, 5‚-AGCCGGAAGATGGGACACTGAG-3‚ (nt 813-792); P2Y 1 sense, 5‚-TCCGATGTGCCCTGATCAAGAC-3‚ (nt 738-759); P2Y 1 antisense, 5‚-ATGAGCCATACCAGCACACTGAC-3‚ (nt 1152-1130); P2Y 2 sense, 5‚-CGCTTCAACGAGGACTTCAAG-TA-3‚ (nt 559-581); P2Y 2 antisense, 5‚-CCCCAGCTCAGG-GAGTGCAGA-3‚ (nt 917-897); P2Y 4 sense, 5‚-GTTCTG-GAGATGGTGATTGTAGG-3‚ (nt 1407-1429); P2Y 4 antisense, 5‚-CAGTATCCCAGGTATCGGTGCA-3‚ (nt 1758-1737); P2Y 6 sense, 5‚-CTACCGTGAGGATTTCAAGCGAC-3‚ (nt 496-518); P2Y 6 antisense, 5‚-CTGGAAGCTAATGCAGGTGAGGA-3‚ (nt 808-786); P2Y 11 sense, 5‚-TGGAGCGCTTCCTCTTCACCTG-3‚ (nt 302-323); P2Y 11 antisense, 5‚-AGTCATGCCTGGGCT-GCGTAG-3‚ (nt 708-688). The PCR reaction included 0.4 ml of template cDNA, 2.5 units of KOD dash polymerase (Toyobo Biochemicals, Osaka, Japan), 1 mM KCl, 6 mM (NH 4 ) 2 SO 4 , 0.1 % Triton X-100, 10 mg ml _1 BSA, 0.2 mM each of deoxynucleotide triphosphates and 4 pmol primers in 20 ml of 120 mM Tris-HCl buffer (pH 8.0).…”
Section: Analysis Of the Expression Of P2 Receptor Subtypes Genesmentioning
confidence: 99%
“…P2Y 1 is a receptor for the endogenous ligands ADP, more than ATP and diadenosine polyphosphates. The P2Y 2,4 receptors are activated with approximately equal potency by ATP as well as UTP [11] . P2Y 6 , showing preference for UDP, is a receptor for pyrimidine which is activated specifically by uridine nucleotides and not by adenine nucleosides or nucleotides [12] .…”
Section: P2 Receptor Subtypesmentioning
confidence: 97%